Analisis Faktor yang Mempengaruhi Pendapatan Usaha Ayam Ras Petelur di Desa Kasang Pudak, Kecamatan Kumpeh Ulu, Kabupaten Muaro Jambi - Hasan Basri; Suherman Suherman; Faradilla Herlin; Ratih Rosita (Ekonomis: Journal of Economics and Business, 2022)
This study aims to analyze the factors that influence the income of laying hens in Kasang Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency. This study uses primary data. The data analysis method used is the method of multiple linear regression analysis (Multiple Regression Analysis). This study found that the cost of vitamins had no significant effect on the income of laying hens. While the variable costs of seeds, feed costs, vaccine costs and labor costs have a significant influence on the income of laying hens in Kasang Pudak Village, Kumpeh Ulu District, Muaro Jambi Regency.